2018
DOI: 10.12991/jrp.2018.119
|View full text |Cite
|
Sign up to set email alerts
|

A study on determining the opinions and attitudes of community pharmacists about non-pharmaceutical medicinal products

Abstract: Social change and changing needs of today's people bring about a service concept that includes both prescription drugs and non-prescription drugs (over the counter medicines and parapharmaceuticals) are offered to clients. Community pharmacists who are the most accessible healthcare providers begin to focus on selling (parapharmaceuticals) non-pharmaceutical medicinal products (NPMPs) that are seen more profitable and require less bureaucratic processes. Assuming that the dilemmas often experienced by communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Similarly, a previous study conducted in Turkey found that the most common non-pharmaceutical products are food supplements (87.3%), and mother and baby products (86.5%), while the least common were sports products and foods (5.7%) (17).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Similarly, a previous study conducted in Turkey found that the most common non-pharmaceutical products are food supplements (87.3%), and mother and baby products (86.5%), while the least common were sports products and foods (5.7%) (17).…”
Section: Discussionmentioning
confidence: 55%
“…Similar findings were reported in a previous study in Turkey where participants believed that non-pharmaceutical products should only be sold in community pharmacies to help with revenue and profits. They also believed that providing counseling for customers on these products is the duty of the pharmacist (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation